2012
DOI: 10.1155/2012/368687
|View full text |Cite
|
Sign up to set email alerts
|

Treatment Adherence with Early Prescription of Long-Acting Injectable Antipsychotics in Recent-Onset Schizophrenia

Abstract: Although response to treatment for the first episode of schizophrenia is generally favourable, nonadherence with the treatment is the first cause of relapse and rehospitalisation within the next few years. Long-acting injectable antipsychotics (LAIAs) combine the advantages of the newer antipsychotics and the long-acting formulation. The evaluation concerns 25 schizophrenic patients hospitalised for the first time, treated with risperidone long-acting injectable (RLAI) associated with reintegration methods, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 45 publications
0
18
0
Order By: Relevance
“…Current guidelines and recommendations on schizophrenia consider LAAPs as drugs of choice for the treatment of schizophrenia patients with recurrent relapses related to non-adherence with antipsychotic medication [11,65,[152][153][154][155][156]. Recent reviews have never been more vocal about their use in early-episode patients for similar reasons (provided schizophrenia has been diagnosed or clinically highly suspected), as these patients ''have more to lose'' [134,[157][158][159][160][161][162][163][164][165][166][167][168][169][170]. LAAPs may, if presented correctly, be more effective for maintaining medication continuity, preventing relapse, reducing the number and duration of rehospitalizations and, when achieving remission, holding this status [161,166,168,169,[171][172][173][174][175].…”
Section: Results Of Descriptivementioning
confidence: 99%
“…Current guidelines and recommendations on schizophrenia consider LAAPs as drugs of choice for the treatment of schizophrenia patients with recurrent relapses related to non-adherence with antipsychotic medication [11,65,[152][153][154][155][156]. Recent reviews have never been more vocal about their use in early-episode patients for similar reasons (provided schizophrenia has been diagnosed or clinically highly suspected), as these patients ''have more to lose'' [134,[157][158][159][160][161][162][163][164][165][166][167][168][169][170]. LAAPs may, if presented correctly, be more effective for maintaining medication continuity, preventing relapse, reducing the number and duration of rehospitalizations and, when achieving remission, holding this status [161,166,168,169,[171][172][173][174][175].…”
Section: Results Of Descriptivementioning
confidence: 99%
“…Among people with schizophrenia, poor medication adherence is a major issue that brings about negative clinical impacts and relapses , which subsequently intensify caregiver burden . Current evidence has indicated that the use of long‐acting injectable antipsychotics (LAIs) can enhance treatment adherence, reduce relapse rates and improve prognosis in people with schizophrenia . Moreover, a recent post hoc analysis revealed that, for people on prior oral antipsychotics after switching to LAIs, caregiver burden was significantly alleviated, with reductions in workdays missed, leisure time affected and time spent in caregiving .…”
Section: Discussionmentioning
confidence: 99%
“…19 Current evidence has indicated that the use of long-acting injectable antipsychotics (LAIs) can enhance treatment adherence, reduce relapse rates and improve prognosis in people with schizophrenia. 20,21 Moreover, a recent post hoc analysis revealed that, for people on prior oral antipsychotics after switching to LAIs, caregiver burden was significantly alleviated, with reductions in workdays missed, leisure time affected and time spent in caregiving. 22 Nevertheless, about one-third of the caregivers in our survey were unsure whether having their ill relative on injectable antipsychotics instead of oral antipsychotics could help improve their own stress ( Table 6).…”
Section: Stress and Burden Faced By Family Caregiversmentioning
confidence: 99%
“…5,[44][45][46][47] A growing body of literature demonstrates that LAIs also are effective for early intervention or when used for first-episode treatment of schizophrenia rather than delaying treatment. [48][49][50][51][52] A higher response rate is associated with initial AP treatment in first episode with significantly less response to subsequent AP treatment. 22,53 Although LAIs may have advantages compared with oral APs, especially with respect to more convenient monitoring of adherence, LAI use often is limited by negative attitudes of health-care professionals, specifically regarding earlier use in the course of therapy.…”
Section: Attitudes and Use Of Early Lai Treatment In Schizophreniamentioning
confidence: 99%
“…Twenty-five schizophrenic patients hospitalized for the first time were treated with a LAI and subsequently followed for up to 18 months. 52 Patients were assessed with CGI and GAF scales. Clinical improvement was associated with fewer relapses and a lower rate of rehospitalization.…”
Section: Clinical Symptoms and Functionmentioning
confidence: 99%